Failure Analysis and Prevention - Ali, Aidy (IntechOpen, 2017)
This book covers recent advancement methods used in analysing the root cause of engineering failures and the proactive suggestion for future failure prevention. The techniques used especially non-destructive testing such X-ray are well described. The failure analysis covers materials for metal and composites for various applications in mechanical, civil and electrical applications. The modes of failures that are well explained include fracture, fatigue, corrosion and high-temperature failure mechanisms. The administrative part of failures is also presented in the chapter of failure rate analysis. The book will bring you on a tour on how to apply mechanical, electrical and civil engineering fundamental concepts and to understand the prediction of root cause of failures. The topics explained comprehensively the reliable test that one should perform in order to investigate the cause of machines, component or material failures at the macroscopic and microscopic level. I hope the material is not too theoretical and you find the case study, the analysis will assist you in tackling your own failure investigation case.